2020
DOI: 10.1007/s10389-020-01317-9
|View full text |Cite
|
Sign up to set email alerts
|

Delay discounting of compliance with containment measures during the COVID-19 outbreak: a survey of the Italian population

Abstract: Aim Unprecedented community containment measures were taken following the recent outbreak of COVID-19 in Italy. The aim of the study was to explore the self-reported future compliance of citizens with such measures and its relationship with potentially impactful psychological variables. Subjects and methods An online survey was completed by 931 people (18-76 years) distributed across the Italian territory. In addition to demographics, five dimensions were measured: self-reported compliance with containment mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…These findings are in line with previous research that demonstrated the relationship between probability discounting and health-related decisions (i.e., Bruce et al, 2016;Jarmolowicz et al, 2018Jarmolowicz et al, , 2019. Recent studies conducted during the COVID-19 pandemic also indicate the relationship between risk-related measures and compliance with health authorities' recommendations (e.g., Byrne et al, 2020;Nese et al, 2020). Byrne et al (2020) conducted a similar study of the US population and found that an increased number of risky choices in a PDQlike task can be a strong predictor of lower adherence to appropriate mask-wearing behavior and social distancing recommendations.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in line with previous research that demonstrated the relationship between probability discounting and health-related decisions (i.e., Bruce et al, 2016;Jarmolowicz et al, 2018Jarmolowicz et al, , 2019. Recent studies conducted during the COVID-19 pandemic also indicate the relationship between risk-related measures and compliance with health authorities' recommendations (e.g., Byrne et al, 2020;Nese et al, 2020). Byrne et al (2020) conducted a similar study of the US population and found that an increased number of risky choices in a PDQlike task can be a strong predictor of lower adherence to appropriate mask-wearing behavior and social distancing recommendations.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, success in diminishing the spread of the disease may largely depend on the compliance of people with the containment measures. Previous studies found that the duration of containment measures plays a crucial role in tackling the spread of the disease as people become less compliant over time [ 15 ]. We, therefore, took a further step and explored the relationship of self-reported citizens’ compliance with other factors such as trust in national government and medical care, fear of getting infected, measures’ perceived effectiveness and restrictiveness, experienced stress during the outbreak, time invested in following the news about the coronavirus outbreak, presence of underlying medical conditions, being infected or having family members infected by the virus, opinion about governments’ response to the outbreak, income loss caused by the crisis, provision of financial compensation for the lost income, and different demographic measures.…”
Section: Introductionmentioning
confidence: 99%
“…With the objective of monitoring symptoms and ensuring early disease detection, quarantine involves the restriction of movement or separation from others of healthy persons who may have been exposed to the disease-causing agent but are not exhibiting any symptoms themselves. As such, all healthy people on whom quarantine is imposed may not accept its restrictions and adhere to them consistently (Nese et al 2020). Although sometimes used interchangeably, quarantine differs from isolation, which applies to people who have been diagnosed with the disease (Apenhorst et al 2020;Chittick et al 2016).…”
mentioning
confidence: 99%